The Impact Of Quality And Cost On Tenant Satisfaction And Loyalty - Agung Ibrahim; Jerry Heikal (Jurnal Scientia, 2024)
This study aims to analyze the impact of quality and cost on tenant satisfaction and loyalty. In an increasingly competitive business environment, retaining loyal customers is a major challenge, especially in the rental property industry. This study uses a quantitative approach with a survey method, collecting data from tenants in the Bakrie Tower building. The Effect of Quality and Cost on Tenant Satisfaction, the results of the study indicate that quality does not have a significant effect on tenant satisfaction, while cost does not have a significant effect on tenant satisfaction. The Effect of Quality and Cost on Tenant Loyalty, The study found that quality does not have a significant effect on tenant loyalty and cost does not have a significant effect on tenant loyalty. However, the results of the study indicate that satisfaction has a positive and significant effect on tenant loyalty. The implications of these findings indicate that tenant satisfaction is a key factor that has a significant effect on tenant loyalty. Tenants who are satisfied with the quality and cost provided are more likely to extend their rental contracts and recommend the building to others. Meanwhile, quality and cost, although not showing a significant direct effect on satisfaction or loyalty, still play an important role in shaping the overall tenant perception and experience. This means that even though tenants are not directly affected by quality or cost, these two factors must still be managed well in order to meet or even exceed tenant expectations.